2019
DOI: 10.1016/j.euroneuro.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body mass index on glucagon-like peptide receptor gene expression in the post mortem brain from individuals with mood and psychotic disorders

Abstract: There is an increasing interest in the putative role of glucagon-like peptide 1 receptor (GLP-1R) agonists as novel therapeutic agents for mental disorders. Herein, we investigated the expressions of GLP-1R and GLP-2R genes, and its relationship with body mass index (BMI), in the post-mortem brain tissue of patients with mood (MD) and psychotic disorders. Brain samples were localized to the dorsolateral prefrontal cortex (dlPFC) (n = 459) and hippocampus (n = 378). After adjustment for age, sex, ethnicity, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Multiple allostatic mediators function as part of a nonlinear network that contributes to the development of AL, including elevated levels of stress hormones (eg, cortisol, epinephrine), proinflammatory markers (eg, C‐reactive protein, Il‐6, TNF‐a), and oxidative stress 12,13 . These then contribute to damaging effects in the brain and other organs, including altered gene expression, 14 telomere shortening 15 and ultimately playing a role in cognitive, cardiovascular, and immune dysfunction as well as in obesity, bone demineralization and atrophy of cerebral nerve cells, whose association with BD is well established 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…Multiple allostatic mediators function as part of a nonlinear network that contributes to the development of AL, including elevated levels of stress hormones (eg, cortisol, epinephrine), proinflammatory markers (eg, C‐reactive protein, Il‐6, TNF‐a), and oxidative stress 12,13 . These then contribute to damaging effects in the brain and other organs, including altered gene expression, 14 telomere shortening 15 and ultimately playing a role in cognitive, cardiovascular, and immune dysfunction as well as in obesity, bone demineralization and atrophy of cerebral nerve cells, whose association with BD is well established 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent review suggested that 24 genes previously associated with cardiometabolic phenotypes are also associated with mood disorders (major depressive disorder (MDD) and BD) 26 . An overview of studies previously investigating the role of genes potentially involved in both BD and obesity or T2D 16,17,21,2736 is reported in Table 1. The majority of these studies investigated variants already known to be associated with T2D or other metabolic phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…increased immobility in a tail-suspension test) [15]. In a human brain study, GLP2R was significantly decreased in the dorsolateral prefrontal cortex, but not dysregulated within the hippocampus (just a decreasing trend of GLP2R) [23]. In contrast, decreased GLP2R resulted in cognitive impairment in Sprague-Dawley rats subjected to chronic cerebral hypoperfusion [22].…”
Section: Discussionmentioning
confidence: 99%